A Review of Adsorption Techniques for Removal of Phosphates from Wastewater - Usman, Mariam Onize; Aturagaba, Godwin; Ntale, Muhammad; Nyakairu, George William (Water Science & Technology, 2022)
Phosphate is considered the main cause of eutrophication and has received considerable attention recently. Several methods have been used for removal of phosphates in water and these include biological treatment, membrane filtration processes, chemical precipitation, and adsorption. Adsorption technology is highly effective in the removal of phosphate from wastewater even at low phosphate concentrations. Nanomaterials/nanoparticles, carbon-based materials (activated carbon and biochar), and their composites have been widely employed for the adsorptive removal and recovery of phosphate from wastewater due to their exceptional properties such as high surface area and high phosphate adsorption properties. This article is a review of the recently reported literature in the field of nanotechnology and activated carbon for the adsorption of phosphate from wastewater. Highlights of the adsorption mechanisms, adsorption behaviour, experimental parameters, effects of co-existing ions, and adsorbent modifications are also discussed.
Keywords: Water treatment; Activated carbon; Adsorption; Eutrophication; Phosphates